Perancangan Mini Akuaponik Portable untuk Meningkatkan Ketahanan Pangan Secara Mandiri Dimasa Pandemi Covid-19 di Lingkungan Rumah - Adiluhung, Hardy; Herlambang, Yanuar; malik, kendall; Fernando, Ferry (SPACEPRO: Product Design Jurnal, 2024)
The COVID-19 pandemic, which forced people to stay at home, has sparked a new culture of gardening in home yards with organic vegetables. As the pandemic continues, we have plenty of free time to stay at home. To relieve boredom, one alternative we can do to make use of this free time is by optimizing our home yards as a source of family food supply. Thus, even though outside activities are still limited, the nutritional needs of the family are still met. Consuming vegetables from our own garden is relatively safer and simultaneously provides a solution for household-scale food fulfillment, which is cost-effective and easy to implement. According to Minister of Agriculture Syahrul from the BKP of Agriculture, gardening activities are one of the strategies in maintaining food security, especially during the COVID-19 pandemic and in facing the dry season. Minister Syahrul has even urged local government leaders to encourage the use of home yards as a source of family food supply, because national food security starts from family food security. The creation of Mini Portable Aquaponics. Aquaponics is an alternative method of growing plants and raising fish within the same container. It is a process where plants utilize nutrients derived from fish waste, which if left in the pond would become toxic to the fish. The plants then function as a vegetation filter that breaks down these toxic substances into harmless substances for the fish, and supplies oxygen to the water used to sustain the fish. With this cycle, a mutually beneficial cycle occurs and for those of us implementing it, it is certainly very advantageous, as the land used is not too extensive.